The moderation effect of vendor support on cloud computing adoption and firm performance - Teh, Raymond; Subramaniam, Anusuiya (Inderscience Publishers, 2024)
This study aims to fill a knowledge gap in prior technology adoption studies by determining the moderating impact of vendor support on cloud computing adoption and firm performance in Malaysian SMEs. This study used 352 Malaysian SMEs as participants in its empirical investigation. The core data for this study were gathered using a quantitative questionnaire, and systematic sampling was utilised to generalise the findings. Vendor support moderates the positive relationship between cloud computing adoption and firm performance, such that the relationship gets stronger as vendor support increases. This study recognises how vendor support plays a moderating role in the relationship between firm performance and cloud computing adoption, in which the relationship becomes stronger as vendor support increases. The research’s findings contributed to and improved the body of knowledge on vendor support’s role as a moderator in studies pertaining to cloud computing adoption.